Enhancing Tax Revenue in Pakistan: Issues and Challenges - Ilyas, Muhammad Aamir (Journal of Pakistan Administration, 2020)
Economic stability is the major concern for all present-day modern states. Indeed, economic strength now overshadows political strength as well as military might on the global political stage. That makes economic security imperative for national security (Beckley, 2010). It is linked with the government’s ability to generate wealth not only from indigenous resources but also through outside world to sustain its economy. Out of all such arrangements, what the governments gets in turn is tax in various forms. Financial administrative pyramid of the state is stemmed with its government’s ability to maximize tax collection. As the governments need funds to invest in development to eradicate poverty and provide public services to the masses to materialize the very idea of a welfare state in which the public pays its due share in the form of taxes and the government rationalize its need-based spending. A good tax system provides these resources to the government to boost investment and growth to help spin the economic wheel through cash ﬂows. Moreover, the fair and transparent tax system also helps in ﬁnancial inclusiveness through technological advancement, encourages healthy competition in diﬀerent sectors by patronizing weak sectors, ensures good governance, addresses income disparities, uneven wealth accumulation and promotes social justice to make an egalitarian society wherein potential at individual level diﬀers but all are provided with equal opportunities.